2018
DOI: 10.29219/fnr.v62.1262
|View full text |Cite
|
Sign up to set email alerts
|

Short-term cactus pear [Opuntia ficus-indica (L.) Mill] fruit supplementation ameliorates the inflammatory profile and is associated with improved antioxidant status among healthy humans

Abstract: BackgroundDietary ingredients and food components are major modifiable factors protecting immune system and preventing the progression of a low-grade chronic inflammation responsible for age-related diseases.ObjectiveOur study explored whether cactus pear (Opuntia ficus-indica, Surfarina cultivar) fruit supplementation modulates plasma inflammatory biomarkers in healthy adults. Correlations between inflammatory parameters and antioxidant status were also assessed in parallel.DesignIn a randomised, 2-period (2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…We show that pre-treatment of Hela cells with Ind at low micromolar concentrations of nutritional relevance, significantly potentiates the cytotoxic action of CDDP, reducing its semi-maximal effective dose. Other studies in healthy men and women have provided a good indication of the potential of this fruit to positively affect the body's redox balance, to decrease oxidative damage to lipids and improve antioxidant status and the response of the immune system [45,46]. Our data suggests that diet intervention with Opuntia cactus pear fruits in patients with cervical cancer undergoing chemotherapy might be considered with the aim to provide Ind as a chemosensitizer of the therapy.…”
Section: Discussionmentioning
confidence: 68%
“…We show that pre-treatment of Hela cells with Ind at low micromolar concentrations of nutritional relevance, significantly potentiates the cytotoxic action of CDDP, reducing its semi-maximal effective dose. Other studies in healthy men and women have provided a good indication of the potential of this fruit to positively affect the body's redox balance, to decrease oxidative damage to lipids and improve antioxidant status and the response of the immune system [45,46]. Our data suggests that diet intervention with Opuntia cactus pear fruits in patients with cervical cancer undergoing chemotherapy might be considered with the aim to provide Ind as a chemosensitizer of the therapy.…”
Section: Discussionmentioning
confidence: 68%
“…Additionally, some authors reported that Opuntia extracts are hepatoprotective and can be used as a nutraceutical to prevent Acetaminophen (APAP)-induced acute liver failure (ALF), which is a serious health problem in developed countries [ 33 ]. Interestingly, there are data in the literature showing that Opuntia extracts can be considered reliable and safe since no toxicity or only low toxicity has been found in animal models [ 34 , 35 ]. Precisely for these reported data about betalain and phenolic compounds’ bioactivities and health-related studies, the composition of these bioactive compounds (betalains and phenolics) of Opuntia stricta var.…”
Section: Discussionmentioning
confidence: 99%
“…Wiese et al [ 11 ] examined the effects of Opuntia ficus indica (OFI) (prickly pear) on alcohol hangover, administered 5 h before alcohol consumption. OFI is used as a dietary supplement for its antioxidant and anti-inflammatory properties [ 12 ]. The authors concluded that the alcohol hangover is mediated by an inflammatory response, as they observed significant correlations between blood C-reactive protein (CRP) concentration and hangover severity.…”
Section: Introductionmentioning
confidence: 99%